SUDUT PANDANG PENGONTRUKSIAN PRO DAN KONTRA DALAM KONSEP SYIRIK DI POLITIK ISLAM - Setiyawan, Joko; Suganda, Rifki (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2023)
This article examines Islamic politics from the Al-Qur'an, Surah Al Imran verse 159 concerning deliberation. This paper argues that deliberation and consensus is one of the values ​​and principles of Islamic politics in the Al-Qur'an. These interpretations even suggest that the Prophet Muhammad SAW, as the leader of the Muslim community at that time, often took decisions suggested by his friends, not based on his own opinion. Several religious figures also stated that politics without a state would not be successful and a state without politics would be impossible, because politics and religion are an inseparable unity, politics itself is simply the application of the absolute mind in humans regarding instruments. It is important in achieving a goal that every human desires, and religion itself has a role in decision making and guiding humans in taking and carrying out tasks in a maslahah way. Therefore, this paper shows that one of the principles of Islamic politics from the Koran is achieving consensus in making decisions that involve many parties and by involving them in decision making